Biofilm Formation in Klebsiella pneumoniae Bacteremia Strains Was Found to be Associated with CC23 and the Presence of wcaG - Zheng, Jin-xin; Lin, Zhi-wei; Chen, Chen; Chen, Zhong; Lin, Fo-jun; Wu, Yang; Yang, Si-yu; Sun, Xiang; Yao, Wei-ming; Li, Duo-yun; Yu, Zhi-jian; Jin, Jia-lin; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Klebsiella pneumoniae bacteremia biofilm traits and distribution characteristics have not been clarified. This study aimed to determine the prevalence and characteristics of K. pneumoniae bacteremia biofilm formation (BF) and to explore the virulence factors associated with K. pneumoniae BF. A total of 250 K. pneumoniae bacteremia isolates were collected from patients in Shenzhen and Shanghai, China. Virulence genes in their genomes were detected by PCR. The isolates were subjected to multilocus sequence typing (MLST) and clonal complex (CC) classification based on housekeeping genes. Biofilms were detected by crystal violet staining. Greater BF was observed in isolates from young adults (<40 years old) than in those from seniors (≥65 years old; P=0.002). MLST yielded 65 different sequence types (STs), with the most represented STs being ST11, ST23, and ST65, and the main CCs were CC23 and CC65; CC23 isolates exhibited greater BF than CC65 or ST11 isolates (both P<0.001). BF was more pronounced among magA(K1), aero+, rmpA+, rmpA2+, allS+, wcaG+, and iutA+ isolates than in isolates that were negative for these virulence factors. Multivariate regression analysis revealed only wcaG as an independent risk factor for BF (odds ratio 11.426, P<0.001), and BF was decreased when wcaG was silenced by antisense RNA. In conclusion, BF in K. pneumoniae bacteremia isolates was found to be associated with CC23 classification and the presence of the wcaG virulence factor gene.